Covid SeveriTy Score PREDICTOR 50: A novel scoring system to assess prognosis in COVID 19 illness - Gundappa, Vivek; Suresh, Parinita; Rajagopalan, Manjari (Asian Journal of Medical Sciences, 2021)
Background: The first case of COVID 19 illness was detected on 31st December 2019 and the disease has progressed globally causing significant morbidity and mortality. The disease initially thought to be a respiratory virus soon showed manifestations involving other systems and diagnosis and treatment of the disease became more complicated. Aims and Objective: This study aims to derive a scoring system based on health records of patients suffering from COVID 19, to help in early triaging of the illness and therefore allowing for early institution of treatment. To establish a scoring system inclusive of clinical, laboratory and radiological parameters to assist in the prognosis of patients afflicted with COVID 19 illness. Materials and Methods: Health records of 138 COVID patients has been included in the study. The scoring system comprises of parameters including Age, Co-morbidities, Shortness of breath, Saturation, Pulse Rate, Respiratory rate, temperature, D dimer, Neutrophil Lymphocyte ratio, Troponin I, Organ involvement, Radiology. The cumulative scoring ranges from 0-16. The mortality rate among the subjects included was 25.4%. Results: All parameters involved were found to be independent risk factors for mortality. Patients were effectively categorized based on the scoring system and mortality found to be associated with increasing scores. This model displayed good discrimination (AUC =0.875) and the sensitivity and specificity of the model was found to be 0.857 and 0.767 respectively. Conclusion: This scoring system has been designed to categorize based on the systemic involvement of the disease and thus would serve as a reliable indicator for prognostic assessment in patients.